FARMERS -HERDERS CONFLICTS IN NIGERIA AND INTERNAL DISPLACEMENT IN NIGERIA - FRANCESCA ESSIEN (International Studies Journal)
The paper examined the frequent violent conflicts between herders and farmers in Nigeria, which have caused the loss of thousands of lives and widespread displacement. Though farmers - herders conflict is not new, the country has been devastated by violent farmer- herder conflict since the early 2000. The paper adopted the descriptive and survey research method. It is theoretical in nature, and drew its arguments from secondary sources. Findings of the study showed that, although the main reason of the conflict is the scarcity of land resources, several other factors such as population pressure, inefficient state mechanisms, climate change, increasing proliferation of arms etc have fueled the conflict in recent years. However, the most immediate trigger to the surge in farmer-herder violence in the country, is the activities of the violent militant groups. Due to easy access to arms, the group who have better weapons try to get what they want by every available means. Consequently, the cycles of farmer-herder violence and reprisal have become increasingly frequent and lethal leading to massive destruction of lives and property and subsequent massive internal displacement. The study also revealed that effort at addressing the conflict have not been effective. The paper concludes that the frequent farmer[1]herder conflict deserves effective government’s response, given the potential how often land disputes rapidly escalate into broader inter-communal conflict and the accompanying destruction of lives and widespread internal displacement.